Assessment of site specific nutrient management on the productivity of wheat at Bhairahawa, Nepal - Yadav, M.; Sah, S. K.; Regmi, A. P.; Marahatta, S. (Journal of Agriculture and Forestry University, 2020)
Low and unbalanced fertilizer application rate are the major factors contributing to the poor yield of wheat in Nepal. The Site Specific Nutrient Management (SSNM) provides the field specific recommendations in a cost effective and precise manner. A field experiment was done at National Wheat Research Program (NWRP), Bhairahawa, Rupandehi, Nepal during 2019- 20 to evaluate the site specific nutrient management approaches in order to enhance wheat productivity. The SSNM dose was determined at NWRP by using omission plot techniques. The calculated SSNM dose (148:65:71 N: P2O5:K2O kg ha-1), was compared with SSNM + Zn + B, (148:65:71:5:1 N: P2O5:K2O Zn : B kg ha-1), Research recommended dose (RRD, 150:50:50 N: P2O5:K2O kg ha-1); National recommended dose (NRD, 100:50:25 N: P2O5:K2O kg ha-1), Nutrients expert dose (NED,110:50:73 N: P2O5:K2O kg ha-1), and farmers dose (FD, 80: 40:15 N: P2O5:K2O kg ha-1) in a RCB design with four replications. The data on growth, yield attributes and yield were collected and analyzed using Genstat Statistical package. Results showed that research recommended dose (RRD) along with SSNM dose and SSNM +Zn +B were statistically similar (p>0.05), but these treatments were comparatively superior over rest of the treatments for yield attributes and yield. Hence it can be concluded that wheat yield can be improved through adoption of SSNM and RRD of fertilizers at Bhairahawa condition.